STRATEGIES TO DEAL WITH POOR LEARNER SAFETY IN THE NORTH-WEST PROVINCE TOWNSHIP SECONDARY SCHOOLS: TOWARDS THE DEVELOPMENT OF A SCHOOL SAFETY STRATEGY - TSHATSHU, UMZIUVUKILE JAMES (Bloemfontein: Central University of Technology, Free State, 2016)
In this research study the phenomenon of learners’ safety in the North-West Province schools was explored. Learners’ safety in South African schools is of paramount importance, as all over in the world, to strive to create an optimum environment that is conducive to effective teaching and learning. An environment where the teachers can teach and learners can learn. The environment that is conducive to learning is characterized by the absence of bullying, corporal punishment, gang violence around the school premises, alcohol and drugs abuse and vandalism of the school property. The realization of learning where there is an improvement in performance is practically possible when learners get the support and protection from home, in addition to the environment that is conducive to effective learning and teaching at school. Homes are expected to be stable environments with no incidents of child abuse. The South African Constitution guarantees equality and equal protection by the law to all, as enshrined in the Bill of Rights. Also enshrined in the Constitution is the protection of human dignity, the right to education and to be educated under safe conditions, and the right to privacy. The creation of the safe school environment resonated in the South African Schools Act, which stipulates the involvement of all stakeholders in schools. The involvement of stakeholders refers to the representation of the parents in School Governing Bodies (SGB) and the learners representation in the Representative Council of Learners (RCL). The duty of the SGB is amongst others, but not limited to budget and drafting of the learner code of conduct. The SGB has to ensure that school safety policy and safety plan takes into consideration the creation of the safe school surroundings. South Africa’s past was characterized by inequality in respect of the education budget, which resulted in township schools being disadvantaged. The schools that were affected most faced challenges such as inadequate control over unauthorized access to school premises, damaged fences or no fence at all, while former model C schools received sufficient budget from the de facto government which could be used to install CCTV cameras, remote-controlled gates and do in-service training of teachers on school safety. In consideration of the aforementioned situation in township schools, research was undertaken to find solution to safety problem. Permission was obtained from the North-West Department of Basic Education, and cooperation and assistance was requested from participating township schools. The study was divided into qualitative and quantitative research for learners and teachers respectively. Questionnaires were given to teachers to complete. Learners and non-teaching staff participated in the focus group interviews purposively sampled in four South African township secondary schools situated in the Dr. Kenneth Kaunda District in the North-West Province. The sampled schools were labeled School A, School B, School C and School D. The focus group responses during interviews highlighted the challenges and the concerns of the learners regarding violence in schools. The number of school teachers who responded to the close-ended questionnaire throughout the North-West Province was 100. The teachers’ responses in the completed and returned questionnaires quantitatively analyzed, showed teachers’ concerns about their safety and the safety of learners in schools. It is envisaged that the proposed strategies to deal with poor learner safety in schools, will be adopted by schools to address the problems of school safety highlighted in this research study.
Published Thesis
Keywords: Constitution; learners; teachers; safety and security; township schools; violence